(untitled) (Statistics, Optimization & Information Computing, 2026)
Optimising resource use for efficiency enhancement can be achieved by balancing multiple objectives/goals (i.e., economic, environmental, and social) that serve sustainable agriculture. Integrating a hybrid model of Goal Programming (GP) and Data Envelopment Analysis (DEA) proposed in this paper improves decision-making in agriculture. This model has addressed the complexities of multiple objective goals in sustainable agriculture. As a case study, the empirical results of such a hybrid model have enhanced the efficiency through optimising resource use by balancing the competing goals. The flexibility of this model makes it adaptable to various scenarios in the agriculture sector.